2011
DOI: 10.1111/j.1365-2893.2011.01550.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a self‐efficacy instrument for hepatitis C antiviral treatment regimens

Abstract: Self-efficacy or confidence in one’s ability to successfully engage in goal-directed behavior has been shown to influence medication adherence across many chronic illnesses. In the present study we investigated the psychometric properties of a self-efficacy instrument used during treatment for chronic hepatitis C viral infection (HCV). Baseline (n=394) and treatment week 24 (n=254) data from the prospective, longitudinal VIRAHEP-C study were examined. Baseline participants were randomly split into two equal si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Strengths of the present study include a large sample size, rigorous prospective study design, measurement of medication adherence using objective electronic monitoring technology, and use of an psychometrically sound measure of HCV treatment self-efficacy 19 . However, a few limitations are noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strengths of the present study include a large sample size, rigorous prospective study design, measurement of medication adherence using objective electronic monitoring technology, and use of an psychometrically sound measure of HCV treatment self-efficacy 19 . However, a few limitations are noted.…”
Section: Discussionmentioning
confidence: 99%
“…A recent factor analysis of the instrument led to refining the measure into a 17-item scale that yielded a Global Self-Efficacy scale (GSE) and four self-efficacy subscales: (a) communication SE (i.e., confidence to communicate with healthcare provider); (b) physical coping SE (i.e., confidence to cope with physical side effects of treatment); (c) psychological coping SE (i.e., confidence to cope with emotional side effects of treatment); and (d) treatment adherence SE (i.e., confidence to take all medication as prescribed and attend doctor visits) (See Table 1) 19 . The revised HCV Treatment Self-Efficacy Survey demonstrated good reliability for the GSE and the four subscales (Cronbach’s α range = .85 to .96) and good discriminant validity with other psychosocial measures 19 . Higher scores on each scale indicate higher levels of self-efficacy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A list of 53 self-management indicators was compiled on the basis of nine articles [ 11 , 20 27 ]. Based on the three tasks of self-management by Corbin and Straus (medical management, role management and emotional management) [ 28 ] and the domains of the already published self-management scale for other chronic disease patients [ 20 , 27 , 29 ], four major domains were identified. Treatment management (14 indicators) refers to medication adherence, symptom monitoring and management.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested the beneficial effects on health outcomes by the implementing self-efficacy to continuing treatment programs [33,34]. However, most of these studies were on life-threatening infectious diseases, such as HIV infection and chronic viral hepatitis [35][36][37][38][39]. In addition, in previous studies, self-efficacy has been correlated with practicing self-care practices for the Table 4 The MASES scores between patients with uncontrolled hypertension and those with well-controlled blood pressure U N C O R R E C T E D P R O O F generality of the results.…”
mentioning
confidence: 99%